Fetus Trafficking in Viet Nam – The New Criminal Method of Human Trafficking - Thuy, Ha Le; Hai Yen, Hoang Thi; Quang Bao, Nguyen (International Journal of Criminology and Sociology, 2021)
When it comes to basic rights of the fetus, including the right to life, theoretical studies around the world on human rights of the fetus still have not reached an agreement on approaches and explanation. Criminal law at the international and national levels still leaves the possibility of protecting the unborn child. Viet Nam’s criminal law is no exception to this trend. In addition, Viet Nam is currently facing human trafficking with new methods and tricks. Children are bought and paid for while still in the womb, then born abroad and given to traffickers. Children are only protected by criminal law for human trafficking if they are born, alive, and detected by the authorities. While the act of trafficking in fetuses is often easily detected by the authorities right from the stage of purchasing and paying, it is not feasible to prosecute this act for human trafficking under the criminal law of Viet Nam. This reduces the criminal law’s ability to suppress crime, at the same time, leaves many fetuses unprotected. Should criminal law be left outside the legal mechanism to protect children while in the fetal stage? This article suggests considering fetus trafficking as a form of human trafficking and to criminalize fetus trafficking. Criminal law should recognize fetus trafficking as a sign of crime or an early stage in the criminal process of human trafficking, because children need special care and protection, including appropriate legal protection before and after birth, due to their physical and mental immaturity.